2018
DOI: 10.1016/j.bpj.2018.03.035
|View full text |Cite
|
Sign up to set email alerts
|

Topological Constraints and Their Conformational Entropic Penalties on RNA Folds

Abstract: Functional RNAs can fold into intricate structures using a number of different secondary and tertiary structural motifs. Many factors contribute to the overall free energy of the target fold. This study aims at quantifying the entropic costs coming from the loss of conformational freedom when the sugar-phosphate backbone is subjected to constraints imposed by secondary and tertiary contacts. Motivated by insights from topology theory, we design a diagrammatic scheme to represent different types of RNA structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 47 publications
2
29
0
Order By: Relevance
“…To carry out the ensemble calculations describe in the remainder of this paper, parameters for hairpin loop initiations as well as two-, three-and four-ways junctions are also required in addition to the library of data presented above. These have been reported in a previous paper (21), and since there are a number of details involved, these earlier results will not be repeated here (but loop initiation free energies using WC pairs are summarized in Fig. 5 compared to R:Y and G:G Hoogsteen pairs).…”
Section: Hairpins and Multiway Junctionsmentioning
confidence: 72%
See 1 more Smart Citation
“…To carry out the ensemble calculations describe in the remainder of this paper, parameters for hairpin loop initiations as well as two-, three-and four-ways junctions are also required in addition to the library of data presented above. These have been reported in a previous paper (21), and since there are a number of details involved, these earlier results will not be repeated here (but loop initiation free energies using WC pairs are summarized in Fig. 5 compared to R:Y and G:G Hoogsteen pairs).…”
Section: Hairpins and Multiway Junctionsmentioning
confidence: 72%
“…This library can be sourced from experimental data or from computer simulations. In a previous paper (21), we have provided a complete and consistent set of Monte Carlo simulation results for the entropy values of hairpins, two-, three-and four-way functions. These correspond to diagrams in which the vertices are all degree 4 (i.e.…”
Section: Monte Carlo Simulationsmentioning
confidence: 99%
“…• ( ), 1 ( ) and 2 ( ), were obtained from the free energies of formation of duplexes, hairpins and 2-way junctions from Monte Carlo data reported in an earlier paper (4). The functional dependence of the loop free energies on the loop lengths were extended beyond the finite-length data available from the simulations by using scaling relationships, yielding the following expressions at = 310 K:…”
Section: Resultsmentioning
confidence: 99%
“…Ref. 4, we demonstrated that all graphs representing RNA folds are Eulerian and because of this property, the structure of every graph must consist of one or more root vertices connected by bridges, except for the one with just a single edge. Some examples are shown in Fig.…”
Section: B Root Verticesmentioning
confidence: 97%
“…Indeed, multiple grammars have been shown to capture major pseudoknot classes while, at the same time, allowing for a characterization of generating functions [36]. An enumeration of designable structures would greatly help in the parametrization of free-energy models, a key aspect of pseudoknot prediction programs which has so far greatly hindered the development of predictive methods [33].…”
Section: Resultsmentioning
confidence: 99%